HUBUNGAN BEBAN KERJA DENGAN KOMUNIKASI TERAPEUTIK PADA DOKTER DI RUMAH SAKIT UMUM DAERAH (RSUD) PASAMAN BARAT - Aulia Nabila; Harry Theozard Fikri; Andhika Anggawira (PT. Hasba Edukasi Mandiri, 2026)
Health is a crucial aspect for every individual, where doctors are the main resource at the hospital to ensure the quality of medical services. Ideally, doctors should master medical competence and therapeutic communication. However, high workloads are often an obstacle in the implementation of such communication. This study aims to determine the relationship between workload and therapeutic communication in doctors at West Pasaman Hospital. This study uses a quantitative method with a total sampling technique of 39 doctors. Data was collected using the workload scale and the therapeutic communication scale. Data analysis used the Shapiro-Wilk normality test which showed normal distributed data (p>0.05) and the linearity test showed a linear relationship (p<0.05). The results of the Pearson Product Moment correlation test showed a correlation coefficient (r) of -0.581 with a significance value of p=0.000 (p<0.01). These findings indicate a significant negative correlation with the strength of the medium-level relationship, so the research hypothesis is accepted. Workload made an effective contribution of 33.8% to therapeutic communication, while the remaining 66.2% was influenced by other factors not studied in this study.